ЛИНГВИСТИК ДАСТУРНИНГ МОРФОЛОГИК ТАҲЛИЛ МОДУЛИ (МОРФОАНАЛИЗАТОР) - Абжалова, М.А. (SCIENCE and SOCIETY, 2021)
This article formally describes the norms of accepting admissible affixes in the system of grammatical categories of words to be analyzed at the morphological stage (morphoanalyzer) of the program for analyzing texts in the Uzbek language, and gives an algorithm for the morphoanalyzer.